(untitled) (Revista Educação, Artes e Inclusão, 2022)
This article is about music education. The objective is to understand how the Family and society influence the choice and learning process of the violin for teenagers from the popular classes of Erechim/RS. Fruit of a qualitative, bibliographical and exploratory research, associated with field research, the study aims to identify social interactions and their influences on the study of the violin. The methodological path relies on bibliographical research related to music education and popular education, as well as semi-structured interviews, focused on the search for necessary subsidies to answer the article’s problem to identify whether families and society are able to influence the choice and the study of the violin. The research subjects are violin students belonging to the popular classes and comprising the age group between 12 and 14 years old, together with their parentes and the conductor of the referred project. The data collected in this research were systematically analyzed in pre-defined categories. Through this research, we concluded that the Family and society beneficially influence the musical study of the interviewed adolescents.